Dysbindin as a novel biomarker for pancreatic ductal adenocarcinoma identified by proteomic profiling. Issue 8 (30th June 2016) - Guo, Xin; Lv, Xiaohui; Fang, Cheng; Lv, Xing; Wang, Fengsong; Wang, Dongmei; Zhao, Jun; Ma, Yueyun; Xue, Yu; Bai, Quan; Yao, Xuebiao; Chen, Yong
Abstract : Pancreatic adenocarcinoma (PDAC) is known to have a poor prognosis partly because of lack of effective biomarkers. In the test set, we investigated dysbindin (DTNBP1) as a potential biomarker for PDAC by comparing preoperative and postoperative serum mass spectrometry (MS) proteomic profilings. Of the included 50 PDAC patients, 42 (positivity of 84.0%) detected a lower MS peak in postoperative serums than preoperative ones which was then identified as dysbindin. In the verification set, receiver operating characteristics (ROC) were used to assess diagnostic efficiency. 550 participants were included in the verification set [250 with PDAC, 80 with benign biliary obstruction (BBO), 70 with chronic pancreatitis (CP) and 150 healthy donors (HD)]. Dysbindin was increased in PDAC patient sera than in all controls. ROC curves revealed the optimum diagnostic cutoff for dysbindin was 699.16 pg/ml [area under curve (AUC) 0.849 (95% CI 0.812–0.885), sensitivity 81.9% and specificity 84.7%]. Raised concentration of dysbindin in sera could differentiate PDAC from BBO, CP and HD. Moreover, dysbindin maintained its diagnostic accuracy for PDAC patients who were CA19‐9 negative [AUC 0.875 (95% CI 0.804–0.945), sensitivity 83.0%, specificity 89.0%] and for patients with benign biliary obstruction [AUC 0.849 (95% CI 0.803–0.894), sensitivity 82.3%, specificity 84.0%].Our discovery of dysbindin may complement measurement of CA19‐9 in the diagnosis of PDAC and help to discriminate PDAC from other pancreatic diseases or begin biliary obstruction. Abstract : What's new? A new biomarker could help diagnose pancreatic cancer early, giving patients a better shot at survival. Since patients experience few symptoms, pancreatic cancer is rarely detected while it is still localized, and has a terrible survival rate. Biomarkers help with diagnosis, but the most commonly used biomarker, CA19‐9, shows up frequently in other gastrointestinal diseases, making it less than ideal. This study compared samples from cancer patients before and after surgery, and identified dysbindin as a reliable marker. Dysbindin showed up more in pancreatic cancer than either healthy controls or other gastrointestinal diseases, suggesting it could complement CA19‐9 well.